The Effect of Fasting Period and Low-Fat Diet on The Testosterone and Follicle Stimulating Hormone of Male Rats (Journal of Pharmaceutical Negative Results, 2022)
Nourishment is essential for the continuity of life in all animals’ kinds. Fasting is one of the world's most widespread fitness and health fads for enhancing their health and simplifying their lives. The low-fat diet is one of the most used applications to maintain the levels of different hormones and therefore decreased the risk of diseases such as cardiovascular disease. Thus, the current study was designed to investigate the effect of a low-Fat Diet in tow period strategy of fasting in 14 hours and 20 hours by using 36 healthy young male albino rats on testosterone and follicle stimulation hormone.